(untitled) (Medical Forum Monthly, 2026)
Objective: To compare the efficacy and safety of thulium fiber laser and Holmium: Yttrium Aluminium Garnet lasers during flexible ureteroscopy for renal calculi. Study Design: Prospective comparative research study.Place and Duration of Study: This study was conducted at the Department of Urology, Al-Kafeel Hospital, Iraq from 15th August 2024 to 31st July 2025. Methods: A research including 193 cases with renal stone of 10-20 mm. The patients were divided into groups group A (thulium fiber laser dusting group) included 95 patients and group B (Holmium: Yttrium Aluminium Garnet l dusting) included 98 patients. The volumetric evaluation and maximal diameter of the stone were determined by non-contrast computed tomography. The operative time and stone free rate for four weeks after the operation were the primary outcomes. Secondary outcomes were perioperative complications, which were categorized according to the Clavien-Dindo classification. Results: In Holmium: Yttrium Aluminium Garnet group, the thulium fiber laser had a considerably lower mean operating time (55±7 vs. 64±9 minutes; mean difference 9 minutes, 95% CI 7–11; p < 0.001). At four weeks, the thulium fiber laser had a higher stone free rate (92%) than the Holmium: Yttrium Aluminium Garnet group (87%), although the difference was not statistically significant (absolute difference 5%, 95% CI –3 to 12; p = 0.22). Only modest Clavien-Dindo grade I–II events and complication rates were similar between groups. Conclusion: During flexible ureteroscopy, thulium fiber laser outperforms Holmium: Yttrium Aluminium Garnet in terms of operational efficiency, safety, and a trend toward greater stone-free rates. These results call for additional validation in multicenter randomized trials and support the broader therapeutic usage of thulium fiber laser.